2016
DOI: 10.1111/jcpp.12517
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial into the effects of neurofeedback, methylphenidate, and physical activity on EEG power spectra in children with ADHD

Abstract: This study provides evidence for specific neurophysiological effects after theta/beta NF and MPH treatment in children with ADHD. However, for NF these effects did not generalize to an active task condition, potentially explaining reduced behavioural effects of NF in the classroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 62 publications
3
54
1
Order By: Relevance
“…Last, cost-effectiveness of neurofeedback could be increased with predictive models of treatment success. Although learning curves were not predictive in the current study, theta power at pre-treatment has been found predictive [27]. It would be worthwhile to search for additive predictive factors.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Last, cost-effectiveness of neurofeedback could be increased with predictive models of treatment success. Although learning curves were not predictive in the current study, theta power at pre-treatment has been found predictive [27]. It would be worthwhile to search for additive predictive factors.…”
Section: Discussionmentioning
confidence: 52%
“…Despite specific instructions during neurofeedback training to prevent excessive muscular tension, it cannot be ruled out that some children used more subtle covert muscular tension to influence the theta/beta ratio. This explanation is further supported by the fact that we could not convincingly demonstrate increases in baseline beta, as recorded before commencing each neurofeedback training, and the lack of chronic beta changes during both rest and task conditions at post-measurement [39]. To reduce potential EMG contamination, higher frequencies may be inhibited, such as in the Lubar protocol [40], or EMG activity could be separately monitored for the major skeletal muscles.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…[8][9][10][11] Two of these experiments reported comparable improvements in attention between the neurofeedback and medication groups yet shied away from collecting neurological measures; 8,9 one showed similar changes in resting-state EEG activity yet neglected to ascertain whether attention actually improved; 10 the other suggested superiority of medication over EEG-neurofeedback in terms of both behaviour and neural activity. 11 Notably, these studies scantily report whether participants learned to modulate the brain signal of interest and thus provide little insight into the neural underpinnings of these effects.…”
mentioning
confidence: 99%